Pengaruh Pelatihan Kerja Dan Motivasi Terhadap Kinerja KaryawanPada Koperasi Simpan Pinjam Dana Amanah Karanganyar - Nugraheni, Andita; , Ma'ruf, Drs., MM (2017)
This study aim to determine the effect of work training and motivation on employee performance saving and loan ooperative Dana Amanah Karanganyar.This research is a quantitative research. The over all population to be sampled inthe study. Extracting information to the 41 employees who were the respondentsin the study, carried out using a questionnaire organized into five Likert scale.Data analysis methods used are validity, reliability test, and test multiple linearregression analysis with t-test, F, and the coefficient of determination (R ²).Hypothesis tests showed the influence of work training and motivation have significant influence with t respectively 4,371 and 4,334. In the F test showed thattogether the variables of work training and motivation have a significant effect on the performance of employees with a probability value of 0.000 (0.000 <0.05).And the coefficient of determination (R ²) amounted to 64,5%.